2022
DOI: 10.3389/fmicb.2022.912473
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Putative Probiotics on Growth, Behavior, and the Gut Microbiome of Farmed Arctic Char (Salvelinus alpinus)

Abstract: Beneficial bacteria promise to promote the health and productivity of farmed fish species. However, the impact on host physiology is largely strain-dependent, and studies on Arctic char (Salvelinus alpinus), a commercially farmed salmonid species, are lacking. In this study, 10 candidate probiotic strains were subjected to in vitro assays, small-scale growth trials, and behavioral analysis with juvenile Arctic char to examine the impact of probiotic supplementation on fish growth, behavior and the gut microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…The fish fed the US diet displayed a trend toward being the least bold and having lower repeatability of the trait of boldness, which could lead to reduced welfare, trends that were less pronounced for the treated ETS and USP diets. Previous studies have shown that manipulating the fish gut microbiome can modulate behavior via the gut–brain axis [ 47 ], and a recent study on farmed Arctic charr ( Salvelinus alpinus ) [ 124 ] showed evidence of bacterial strains influencing the response to stress and growth, where fish fed with E. thailandicus 04-394 and L. brevis ISCAR-07433 displayed an increase in motility and slower growth, which can be interpreted as a lower stress coping ability. Selecting for personality has been identified as a valuable tool to reduce chronic stress in captive fish, where bolder individuals are usually more resistant to chronic stress [ 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fish fed the US diet displayed a trend toward being the least bold and having lower repeatability of the trait of boldness, which could lead to reduced welfare, trends that were less pronounced for the treated ETS and USP diets. Previous studies have shown that manipulating the fish gut microbiome can modulate behavior via the gut–brain axis [ 47 ], and a recent study on farmed Arctic charr ( Salvelinus alpinus ) [ 124 ] showed evidence of bacterial strains influencing the response to stress and growth, where fish fed with E. thailandicus 04-394 and L. brevis ISCAR-07433 displayed an increase in motility and slower growth, which can be interpreted as a lower stress coping ability. Selecting for personality has been identified as a valuable tool to reduce chronic stress in captive fish, where bolder individuals are usually more resistant to chronic stress [ 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…Juvenile Arctic char ( S. alpinus ) were collected from an ongoing feeding trial (Knobloch et al 2022 ) at 104 days posthatch (dph) (T0, N = 22), 132 dph (T1, N = 15), and 157 dph (T2, N = 15). Before the beginning of the feeding trial (T0), one fish was collected from each of the 22 experimental tanks.…”
Section: Methodsmentioning
confidence: 99%
“…At T1 and T2, five fish were collected from each of the three replicate control tanks. All fish had received the same control diet, consisting of fish meal, fish oil, gelatinized wheat, minerals, and vitamins as described in Knobloch et al ( 2022 ), and were reared under identical conditions with a continuous freshwater exchange and a water temperature of 8.6 ± 0.5°C. The fish were fasted 12 h prior to weighing and sample collection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In aquaculture, probiotics can be defined as live micro-organisms, usually bacteria or yeasts, that, when administered through feed or the rearing environment, confer beneficial effects to the host such as protection against ichthyopathogens, the stimulation of the immune system, competition for adhesion sites in the mucosa, improved tolerance to stress, host nutrition enhancement, and water quality improvement [14][15][16][17][18]. Usually, both the host and the rearing environment have been regarded as the most suitable sources for the isolation of probiotic candidates for larviculture.…”
Section: Introductionmentioning
confidence: 99%